AN INVESTIGATION INTO KRUKENBERG’S TUMOUR AT A TERTIARY REFERRAL CENTRE: A COHORT STUDY. - Kamal, Samarina (Student’s Journal of Health Research Africa, 2024)
Objectives This study aims to distinguish women having Krukenberg cancer and confirm the significance of non-curative surgery Methods In this retrospective study, 107 patients with Krukenberg cancer as well as ovarian tumors were chosen from hospital records. The radiological studies were carried out by means of pre-operative abdominal/pelvic CT scans. The radiology results after evaluation by a diagnostic radiologist provided details on the size of the tumor, its metastases, the involvement of lymph nodes, and ascites extracted. Additionally, CT images were processed and standardized for analysis, including tumor segmentation and image resizing. Results The study included 107 patients diagnosed with Krukenberg tumors (n=58) or ovarian tumors (n=49), with 72.5% diagnosed at stage IV, highlighting advanced disease. Surgical resection was performed in 73.3% of patients, emphasizing its importance in management. Metachronous tumors occurred in 54.2% of patients, indicating metastasis of the ovarian tumor post-primary tumor diagnosis. Treatment responses varied, with 38.5% responding to systemic therapy, while 70.7 % experienced disease progression. Additionally, age and elevated CA125 levels (OR: 2.49; 95% CI: 1.50–5.43; p < 0.001; OR: 1.61; 95% CI: 1.37–2.60; p = 0.005) showed significant associations with Krukenberg tumors in multivariable analysis. Conclusion The study underscores the significance of surgical resection and highlights the diagnostic value of CA125 levels in managing Krukenberg tumors. Recommendation The study recommends further investigation into the utility of CA125 levels as a diagnostic marker and emphasizes the importance of timely surgical intervention in the management of Krukenberg tumors.